2007
DOI: 10.1007/s00228-006-0220-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topiramate on energy balance in obese men: a 6-month double-blind randomized placebo-controlled study with a 6-month open-label extension

Abstract: Topiramate treatment produced significantly greater weight loss than placebo and the majority of this loss was explained by a decrease in body fat stores. Most of the weight loss effect produced by TPM therapy was observed within a period of 6 months. Finally, TPM treatment had an impact on energy balance through a reduction in food intake that appears to have created an energy deficit of about 30,000-40,000 kcal compared with treatment with the placebo over 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 22 publications
4
30
0
1
Order By: Relevance
“…It is currently not fully known how topiramate exerts its effect on body weight, but several mechanisms have been proposed (32). For example, studies have shown that topiramate decreases food intake in animals as well as in humans (8,33). Furthermore, animal studies showed that topiramate treatment can increase energy expenditure and decrease energetic efficiency (34,35).…”
Section: Adverse Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently not fully known how topiramate exerts its effect on body weight, but several mechanisms have been proposed (32). For example, studies have shown that topiramate decreases food intake in animals as well as in humans (8,33). Furthermore, animal studies showed that topiramate treatment can increase energy expenditure and decrease energetic efficiency (34,35).…”
Section: Adverse Eventmentioning
confidence: 99%
“…Furthermore, animal studies showed that topiramate treatment can increase energy expenditure and decrease energetic efficiency (34,35). This, however, was not demonstrated in humans (33). Why topiramate causes weight reduction in some patients but not in others is also up for debate.…”
Section: Adverse Eventmentioning
confidence: 99%
“…Reduced hunger and appetite during weight loss could reflect cumulative anorectic effects of topiramate, balanced against the orexigenic effects of topiramate-promoted fat loss or related to energy deficit through other mechanisms. 27 This would favor persistence of weight loss. Regarding energy expenditure, topiramate might decrease energy storage and usage efficiency and thus increase energy expenditure.…”
Section: Topiramate (Tpm)mentioning
confidence: 99%
“…Regarding energy expenditure, topiramate might decrease energy storage and usage efficiency and thus increase energy expenditure. 27 Topiramate might inhibit adipocyte mitochondrial carbonic anhydrase isozyme V, 28 thereby inhibiting carbonic anhydrase-mediated lipogenesis. 29,30 Topiramate probably also affects lipoprotein lipase activity in white and brown adipose tissue, which would limit free fatty acid substrate for lipogenesis and may increase thermogenesis.…”
Section: Topiramate (Tpm)mentioning
confidence: 99%
“…Sir, We read with great interest the paper of Tremblay and others [1] on topiramate's effect on weight, energy balance, appetite and satiety. They studied topiramate-induced weight loss (WL) in obese males who were, however, instructed not to start any diet or exercise program intended to induce WL during the course of the study.…”
mentioning
confidence: 99%